Civil Society and the Pluralization of African Philanthropy: A Case of Back to the Future?. (February 2022) - Fowler, Alan
This article explores the prospect that alteration in the profile of resources relied on by African civil society will affect citizen's relationships with their states. Description and analysis advance an ontological narrative of Africa's pre- to postcolonial gift-giving, or "gifting" rapidly diverging in this century. Gifting processes exhibit both non-agonistic "horizontal" and agonistic "vertical" dimensions, connecting Ekeh's "two moral publics" that characterize the continent's neo-patrimonial political systems. The unfolding context exhibits pluralization, localization, and privatization of financing that a historically determined, multilayered African civil society can access and self-provide. The notion of "civic space" guides analysis of intersections between gifting and African civil society, in relation to governance, resourcing, and equity. A conclusion is that gains in scale and diversity of domestication in gifting to and by civil society are unlikely to bring significant change to Africa's politics: more likely is a governance future resembling the past.